Effect of Doctor’s Personality, Job Characteristic, Payment Method, Facility, on Performance and Quality of Doctor Service - Heni Hastuti; Didik Tamtomo; Endang Sutisna Sulaeman (Journal of Health Policy and Management, 2017)
Background: Doctors generally do not work permanently at hospitals. Doctors are expected to deliver quality medical service at the hospitals. However, hospitals often find it difficult to exercise efective managerial control over the quality of medical services. This study aimed to investigate the effect of doctor’s personality, job characteristic, payment method, facility, on performance and quality of doctor service.Subjects and Method: This was an analytic observational study using cross-sectional design. The study was carried out at Dr. Moewardi  Hospital and PKU Muhammadiyah Hospital, Surakarta, from March to May 2017. A sample 182 study subjects consisting of 26 doctors, 26 nurses, and 130 patients, were selected for this study by simple random sampling. The dependent variable was quality of doctor service. The independent variables were doctor’s personality (extrovert vs. introvert), doctor’s carefulness, proactive attitude, self-efficacy, autonomy, performance feedback, supervisor support, payment method, work site (private vs. public), and performance. Questionnaire was used to collect data. Path analysis was employed to analyze the data.Results: Good quality of doctor service was directly affected by good performance (b=0.64, SE=0.11, p<0.001), private work site (b= 2.85, SE=0.66, p<0.001), and strong self-efficacy (b=0.21, SE=0.07, p=0.006). Good work performance  was affected by extrovert personality (b=0.08, SE= 0.06, p=0.186), careful attitude (b=0.30; SE=0.09; p=0.001), proactive personality (b=−0.17; SE=0.05; p=0.001), strong self-efficacy (b=0.27; SE=0.07; p<0.001), autonomy (b=0.16; SE=0.06; p=0.015), performance feedback (b=0.43; SE=0.13, p<0.001), supervisor support  (b=0.14, SE=0.06, p=0.018), payment method (INA CBGs) (b= −2.29; SE= 0.66; p<0.001), and private work site (b= -0.26, SE= 0.68, p=0.696).Conclusion: Good quality of doctor service is directly affected by good performance, private work site, and strong self-efficacy.Keywords: quality, doctor’s service, performance, path analysisCorrespondence: Heni Hastuti. Masters Program in Public Health, Sebelas Maret University, Surakarta. Email: henihastuti.1988@gmail.com Mobile: +6281904534310.The Journal of Health Policy and Management (2017), 2(1): 42-55https://doi.org/10.26911/thejhpm.2017.02.01.04